2022
DOI: 10.1159/000525552
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy-Assisted 2-Port Fetoscopic Repair of Spina Bifida Aperta: Report of a Single-Center Experience in Paris, France

Abstract: Background: Given the maternal morbidity of open fetal surgery, the development of prenatal fetoscopic repair for spina bifida aperta (SBA) is encouraged. Objective: We hereby report the early results from our center, using a laparotomy-assisted CO2-fetoscopic approach. Methods: This study was conducted in patients with an SBA<T1 and >S1, <26 weeks’ of gestation, with Chiari II. Fetoscopic repair was performed using 2 operating trocars in the uterus exteriorized through a transverse laparotomy. Endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…To report on our experience and then based on the IDEAL recommendations confirm the replication of the safety of this hybrid fetoscopic method, as already reported by other centers [22,23]. Other studies report the outcome of small groups of patients (seven cases, one case) but do not describe the implementation of the surgical approach or the establishment of a multidisciplinary team [24,25]. As part of our training, we were supervised directly by experts from the fetal team of TCH; in addition, essential requirements had to be met prior to the start of the surgery to join the consortium [20].…”
Section: What Is the Aim Of This Current Study?supporting
confidence: 71%
“…To report on our experience and then based on the IDEAL recommendations confirm the replication of the safety of this hybrid fetoscopic method, as already reported by other centers [22,23]. Other studies report the outcome of small groups of patients (seven cases, one case) but do not describe the implementation of the surgical approach or the establishment of a multidisciplinary team [24,25]. As part of our training, we were supervised directly by experts from the fetal team of TCH; in addition, essential requirements had to be met prior to the start of the surgery to join the consortium [20].…”
Section: What Is the Aim Of This Current Study?supporting
confidence: 71%
“…[5][6][7] The latest advance in prenatal surgical repair is to close the defect by fetoscopy, a minimally invasive technique that reduces maternal and foetal morbidity of in utero open surgical repair. 4,[8][9][10] Although foetal surgical repair has been shown to reduce the risk of hydrocephalus and possibly improve lower limb motor function, it can only be performed after skin keratinization (i.e., after 20 weeks). However, given the progression of neuronal loss beginning early in foetal life, 11 a procedure performed earlier in pregnancy would significantly improve the outcomes of prenatal repair.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that prenatal coverage of the defect improves neurological function and reduces morbidity from hydrocephalus and Arnold–Chiari II malformation by reversal of hindbrain herniation 5–7 . The latest advance in prenatal surgical repair is to close the defect by fetoscopy, a minimally invasive technique that reduces maternal and foetal morbidity of in utero open surgical repair 4,8–10 . Although foetal surgical repair has been shown to reduce the risk of hydrocephalus and possibly improve lower limb motor function, it can only be performed after skin keratinization (i.e., after 20 weeks).…”
Section: Introductionmentioning
confidence: 99%